THE TEACHER TO THE CREATIVE COMMONS LICENSE: EDUCATIONAL IMPLICATIONS IN SCHOOL 2.0. - Juan José Leiva Olivenza (Ediciones Universidad de Salamanca, 2011)
We currently live in an era of constant changes in the world of culture and education. In recent decades we are witnessing an evolution towards a knowledge society where the expansion is key and critical use of Information Technologies and Communication Technologies (ICTs) to all areas of life. The current technological paradigm substantial change in the teacher professional profile and are essential skills and knowledge that teachers need to help school students to build digital competence capable of addressing the challenge of a networked society and ongoing social and technological change. In this context, teachers must understand the technological and educational implications of the Creative Commons licenses as an opportunity to promote digital literacy in school 2.0.